Conspicuity of Peripheral Zone Prostate Cancer on Computed Diffusion-Weighted Imaging: Comparison of cDWI1500, cDWI2000, and cDWI3000. (1st December 2014) - Vural, Metin; Ertaş, Gökhan; Onay, Aslıhan; Acar, Ömer; Esen, Tarık; Sağlıcan, Yeşim; Zengingönül, Hale Pınar; Akpek, Sergin
Abstract : Introduction and Objective . Disadvantages associated with direct high b -value measurements may be avoided with use of computed diffusion-weighted imaging (cDWI). The purpose of this study is to assess the diagnostic performance of cDWI image sets calculated for high b -values of 1500, 2000, and 3000 s/mm 2 . Materials and Methods . Twenty-eight patients who underwent multiparametric MRI of the prostate and radical prostatectomy consecutively were enrolled in this retrospective study. Using a software developed at our institute, cDWI1500, cDWI2000, and cDWI3000 image sets were generated by fitting a monoexponential model. Index lesions on cDWI image sets were scored by two radiologists in consensus considering lesion conspicuity, suppression of background prostate tissue, distortion, image set preferability, and contrast ratio measurements were performed. Results . Lesion detection rates are the same for computed b -values of 2000 and 3000 s/mm 2 and are better than b -values of 1500 s/mm 2 . Best lesion conspicuity and best background prostate tissue suppression are provided by cDWI3000 image set. cDWI2000 image set provides the best zonal anatomical delineation and less distortion and was chosen as the most preferred image set. Average contrast ratio measured on these image sets shows almost a linear relation with the b -values. Conclusion. cDWI2000 image set with similar conspicuity and the same lesion detection rate, but better zonal anatomical delineation, and less distortion, was chosen as the preferable image set.